FILSAFAT ILMU EKONOMI DAN MANAJEMEN UMKM : PERAN ECO-INDUSTRIAL PARK (EIP) PADA INDUSTRI KECIL MENENGAH UNTUK MEWUJUDKAN GREEN INDUSTRY YANG EFEKTIF DAN EFISIEN - Sumitro Sumitro (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2015)
Free trade agreement of ASEAN Economic Community (AEC) immediately will beimplemented in the region. The four pillars of the AEC concept is a reference in the enforcementprocess. All member-states have made preparations including Indonesia. Small and Medium-sizedEnterprises also make preparations. The preparation of the Indonesian government in the deal andhow the measures taken to protect Small and Medium-sized Enterprises is a discussion in the review ofthis article. Policies made by the government, including the measures taken for businesses Small andMedium-sized Enterprises, still found some difficulties in implementation. Because entirely not goingwell then the nomination acceleration trade policies comprehensively needs to be activated immediatelyso that the various policy papers that the government made will be able to work together withentreperenurs. This study also found unrediness of national products, especially Small and Mediumsized Enterprises in competing due to human resources, inadequate infrastructure and the investmentclimate